Comparative analysis of clinical and imaging data of first-attack neuromyelitis optica spectrum disorders with and without connective tissue disease - Yao, Yaobing; Yang, Xuan; Zhou, Yongyan; Xie, Haojie; Duan, Ranran; Jing, Lijun; Li, Yanfei; Guan, Wenjuan; Teng, Junfang; Jia, Yanjie (Frontiers in Neurology, 2022)
Background: The coexistence of neuromyelitis optica spectrum disorder (NMOSD) and connective tissue disease (CTD) is well recognized. The purpose of this study was to investigate and compare the characteristics of first attack NMOSD with and without CTD. Methods: A total of 113 Patients with NMOSD were included and were divided into two groups based on the presence of co-occurring CTD. Their demographic, clinical, laboratory, and image characteristics were obtained through inpatient medical records and follow-ups. Kaplan–Meier survival analysis was used to analyze the effect of CTD in NMOSD patients at the time of first recurrence. The risk factors that could predict complications of NMOSD with CTD was analyzed by binary logistic regression. The ability of homocysteine (Hcy) to predict the coexistence of NMOSD and CTD was analyzed and evaluated by the receiver operating characteristic curve. Results: The demographic data, clinical features, cerebrospinal fluid analysis, and MRI findings, except relapse events (including relapse rate, number of recurrences, and time of first recurrence), were similar between the two groups. The serum lymphocyte-to-monocyte ratio and albumin levels were lower (P < 0.05), while serum erythrocyte sedimentation rate and Hcy levels were higher in patients with NMOSD with CTD than in those without CTD (P < 0.001). Kaplan–Meier survival analysis showed that the time of first recurrence in NMOSD patients complicated with CTD was earlier than that of without CTD (log rank test P = 0.035). Logistic regression revealed that serum Hcy levels (OR 1.296, 95% CI, 1.050‒1.601, P = 0.016) were independently associated with the occurrence of NMOSD with CTD. The receiver operating characteristic curve area was 0.738 (95% CI, 0.616‒0.859; P < 0.001) for Hcy levels. Considering the Hcy concentration of 14.07 μmol/L as the cutoff value, the sensitivity and specificity of predicting the coexistence of first-attack NMOSD and CTD were 56% and 89.8%, respectively. Conclusions: When the first-attack NMOSD patients are complicated with CTD, they have a higher recurrence rate, more recurrences, earlier first recurrence, higher serum Hcy levels, and enhanced systemic inflammatory reactions. Furthermore, Hcy levels may help to screen for CTD in patients with first-attack NMOSD.